ISOKINETIC ECCENTRIC TRAINING IS BETTER THAN CONSTANT LOAD ECCENTRIC TRAINING ON THE QUADRICEPS REHABILITATION FOLLOWING PARTIAL MENISCECTOMY: A RANDOMIZED CLINICAL TRIAL (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2019)
OBJECTIVES: To compare the effects of conventional (constant load) eccentric training and isokinetic eccentric training on quadriceps muscle mass, strength and functional performance in recreational athletes following partial meniscectomy. METHODS: Thirty two recreational male athletes (~27 years old) undergoing partial meniscectomy received a standard rehabilitation program. Volunteers were randomized to conventional group (CG; n=16) or isokinetic group (IG; n=16) to be engaged in a 6-week (2 sessions/week) quadriceps eccentric training program at the extensor chair or at the isokinetic dynamometer, respectively. Assessments of quadriceps muscle mass, strength and functionality were performed before and after training programs. RESULTS: Training programs produced higher changes in IG compared to CG in all outcomes (p